Negative Stigma of Society Towards Covid-19 Patients - Gherice E Serumena; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The increase in the COVID-19 pandemic has made the public even more anxious with the amount of fake news circulating on social media, resulting in a negative stigma for people who have been confirmed to have COVID-19 or have close contacts. This causes the spread of disease in the community is increasingly out of control. To find out the picture of community stigma against Covid-19 patients in Indonesia from the results of previous studies in 5 related journals. This study uses an analytic review literature study. The secondary data search method is sourced from scientific journals Results in The high stigmatization of suspected patients, close contacts, and confirmed COVID-19 The COVID-19 pandemic in Indonesia shifted the cultural value of helping each other in society, stigma and suspicion emerged in socializing behavior such as being rejected and ostracized because of the potential to spread the virus in the community. Negative stigma against positive COVID-19 sufferers must be annulled with optimal health literacy from various parties, especially stakeholders in areas that have the potential for transmission. And provide support and motivation so that the spirit to heal. Bad social behavior can lead to stigmas against others, such as isolating and refusing patients, families, or corpses with suspected, probable, and confirmed cases of COVID-19, discriminating against certain ethnicities or people who move from one area to another as virus carriers. Internal medical personnel also often receive the same treatment regarding stigma from some communities. It is necessary to develop community character to fight stigmatization, through education and communication regarding the role of society in dealing with social situations amid the global Covid-19 pandemic.